Neural correlates of altered reward-driven attention in chronic pain and opioid use - Su Hyoun Park; Anne K. Baker; Katherine T. Martucci (Scientific Reports)
Abstract While attentional processing of reward may be altered in chronic pain, the neural circuits underlying these alterations, and impact from opioid use have remained unclear. To investigate the neural representation of attentional processing in chronic pain, we collected brain fMRI data from patients (fibromyalgia; taking vs. not taking opioids) vs. pain-free controls during performance of a reward task. We selected the inferior frontal gyrus (IFG) and lateral occipital cortex (LOC) as attention-relevant regions of interest. While IFG and LOC responses were not significantly different across groups, we observed decreased IFG response during reward anticipation in patients (uncorrected, p = 0.05). When evaluating LOC-IFG functional connectivity, vs. controls, we observed significantly reduced LOC-IFG connectivity in patients (p-FDR corrected = 0.026), driven by reduced connectivity in non-opioid patients. Further in non-opioid patients, we observed that the relationship between LOC-IFG connectivity and task performance was moderated by pain duration (post-hoc moderation analysis, p = 0.031), indicating cumulative influences of pain duration on attentional processing behavior/circuits. As suggested by our results, attentional processing of reward is altered in fibromyalgia within LOC-IFG brain circuits, possibly to a lesser degree in patients who take opioids, and with potential cumulative effects of longer pain duration.